Strategi Pendidikan Lembaga Masjid dalam Mengembangkan Spiritualitas Jamaah: Studi terhadap Program Makan Siang Gratis - Fakhri Abdullah Mundzir (Kamaya: Jurnal Ilmu Agama, 2026)
This study is motivated by the need to revitalize the role of mosques as centers of Islamic education that go beyond ritual worship by strengthening the spiritual and social dimensions of congregants. This research aims to analyze the educational strategies implemented by Baitul Huda Mosque in developing congregants’ spirituality through its Free Lunch Program. The study employs a qualitative approach with a case study design, utilizing observations, in-depth interviews, and documentation of mosque activities. The findings reveal that the program effectively cultivates Islamic values such as empathy, brotherhood, sincerity, and gratitude by integrating social services with Qur’anic learning and moral instruction. The novelty of this research lies in its formulation of an integrative educational strategy model that combines spiritual and social approaches within a daily philanthropic activity. This study contributes theoretically to the development of community-based Islamic education and offers practical insights for other mosques seeking to design inclusive and sustainable spiritual development programs.